Hubungan Tingkat Pengetahuan dengan Perilaku Pemeriksaan Inspeksi Visual Asam Asetat pada Wanita Usia Subur yang Sudah Menikah di Wilayah Kerja Puskesmas Sukawati II - Luh Gde Sita Maharani; Dewa Ayu Putu Ratna Juwita; Anny Eka Pratiwi (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2023)
Cervical cancer is the growth of abnormally dividing cells that can invade the tissue (epithelium) of the cervix due to a virus. Early detection of the human papilloma virus plays an important role. Acetic acid visual inspection is an examination by observing the cervix with a speculum, then applying acetic acid. The aim of this study was to determine the relationship between married women of reproductive age's knowledge level and the behavior of acetic acid visual inspection as an early detection of cervical cancer in the Sukawati ll community health center working area. This study used an analytic method design with a cross sectional approach, which used 126 samples using consecutive sampling technique. Data were collected using questionnaires and then analyzed univariate, bivariate and multivariate using IBM SPSSÂ® version 25. Based on the Chi-Square test, there was a significant relationship between the level of knowledge (p < 0.01), attitude (p < 0.01), latest education (p < 0.01), family support (p < 0.02), residential access (p < 0.03), affordability (p < 0.01), and friend support (p < 0.01). While the variables of health worker support and access to information did not have a significant relationship. This study concluded that the level of knowledge has a significant relationship with acetic acid visual inspection inspection behavior (p < 0.01).